Does Checking the Placement of Ossicular Prostheses via the Posterior Tympanotomy Improve Hearing Results After Cholesteatoma Surgery?. Issue 9 (October 2015) - Roux, Allan; Bakhos, David; Villeneuve, Alexandre; Hermann, Ruben; Suy, Paul; Lescanne, Emmanuel; Truy, Eric
<x xml:space="preserve">Abstract</x> Introduction: Posterior tympanotomy (PT) is often performed during the surgical management of middle ear cholesteatoma with extension in the retrotympanum area. This PT can also be used to control the right position of the ossicular prosthesis masked by the tympanic membrane reconstruction. Objective: To compare audiologic results after ossiculoplasty performed via the outer ear canal and via the PT for patients with cholesteatoma. Materials and Methods: Retrospective chart reviews were performed for 68 patients (68 ears) with cholesteatoma who underwent titanium ossicular prosthesis surgery between January 2007 and January 2011. We compared audiologic results between two groups: the WPT group (the group without checking the prosthesis via the PT) and the PT group (the group with placing and/or checking the prosthesis via the PT). A postoperative pure-tone average air-bone gap of 20 dB or less was considered a successful hearing result. Results: Of the patients who underwent canal wall-up mastoidectomy for cholesteatoma with ossicular chain reconstruction by titanium prosthesis, 36 patients (20 total ossicular replacement prosthesis [TORP], 16 partial ossicular replacement prosthesis [PORP]) were in the PT group and 32 patients (16 TORP, 16 PORP) were in the WPT group. The global success rate (defined as a mean residual air-bone gap < 20 dB) was 50% in the WPT group (56% in the subgroup PORP, 44% in the subgroup TORP) and 42% in the PT group (62% in PORP, 25% in TORP). There was no case with extrusion of the prosthesis in either group. No facial palsy occurred during the postoperative period for either group. Conclusion: Control of ossicular prosthesis positioning via the PT does not improve hearing results after ossicular chain reconstruction in cholesteatoma surgery. However, this approach can be used during a second-stage procedure that avoids incisions within the external ear canal.